Was war falsch am Merkantilismus? - Peter Spahn (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
Mercantilist theories and policies in early capitalism have been criticized for confusing microeconomic and macroeconomic sources of wealth, for misunderstanding the benefits of free trade, and for overrating the role of money. This paper aims to reconstruct the rationality of mercantilism as an efficient strategy of economic development. It presents a critical assessment of David Hume's specie flow mechanism that counts as a major rebuttal of mercantilism and collects insights of early writers into the working of a monetary economy.
urn:nbn:de:bsz:100-opus-15490
Keywords: B1; F4; N1; 330; trade war; trade surplus; specie flow mechanism; bank reserves; development